Analysis on Emergency Treatment Effect of Tritium Leakage Accident in the Nuclear Reactor Under Different Ventilation Conditions - Li, Changjun; Cai, Xingfu; Xiao, Mingqing; Huo, Yonggang; Xu, Peng; Li, Sufen (Frontiers in Energy Research, 2022)
The high pressure tritium leakage is a typical nuclear leakage accident, which can cause radioactive harm. Aiming at the tritium leakage problem in high pressure vessel of nuclear reactor, the paper installs a typical tritium leakage scenario and establishes the thermodynamic model of tritium leakage behavior to describe the transient process of tritium leakage. And then, setting up six different ventilation scenes, carrying out the numerical simulation of tritium migration and mixing behavior based on Fluent, analyzing the effect of different ventilation scenes on tritium removal efficiency. The result shows that different ventilation scenes will form different swirl distribution, the more complex the swirl distribution is, the faster the tritium concentration decreases. The shortest time required to decrease tritium concentration in space to background level at the ventilation rate of 1m3·s-1 is about 830s and the longest time is about 1100s. The overall tritium removal efficiency can be effectively improved when the swirl concentration distribution area is opposite to the exhaust outlet position. The setting method of ventilation is optimized, which provides technical support for the emergency treatment of tritium leakage accident in room.